EFFECT OF ADDING DIFFERENT LEVELS OF DAMASCUS FLOWERS WATER (ROSA DAMASCENA) TO BROILER CHICKENS DRINKING WATER ON CARCASS AND HISTOLOGICAL CHARACTERISTICS - Mahmoud K. J.,; Al-Hassani, A. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Through previous studies, we have found only a small number of studies that have discovered the effects and importance of rose water for animals. The aim of this research was to evaluate the effect of various concentrations of aqueous extract of damask flowers water on body weight, carcass weight and measurements, and some histological characteristics of the jejunum and large intestine of broiler chickens. The commercial Ross308 broiler chicks were randomly divided which it number is 250 chicks into 5 groups at the first day (50 Chicks for each group). The chicks were fed a starter diet from the age of 1-10 days, a growth diet from the age of 24-14 days, and a finishing diet from the age of 25-42 days. In treatment T1 plain water was used without adding (the control treatment), while in treatment T2 and T3, damask flowers water was added to the drinking water at a rate of 5% and 10% for 24 hours, and in treatment T4 and T5, damask flowers water was added to the drinking water at a rate of 5% and 10% for a period of 24 hours. 5% and 10% for 12 hours only, respectively. The results showed that in both coefficients T2 and T5, there was a statistically significant increase in some of the main and secondary carcass qualities of the coefficients under study, while there was a varying effect of the transaction on some histological qualities of the broiler carcasses under study.